Penyelidikan struktur batuan menggunakan metoda geolistrik tahanan jenis konfigurasi wenner inversi robust constraint di Jorong Koto Baru Nagari Aie Dingin Kabupaten Solok - Sri mulyani (PILLAR OF PHYSICS, 2016)
Rock structure  in Jorong Koto Baru has not been known and analyzed. Furthermore, it is significant to conduct a research which was purposed to find the structure of rock in Jorong Koto Baru, Nagari Aie Dingin, Kabupaten Solok. The measurement used Resistivity Geoelectrical method with Wenner Configuration. The data were analyzed and interpreted by using Robust Constrain Inversion in software Res2dinv to obtain 2D model. This research indicated that there are five types of rocks which had formed  in Jorong Koto Baru, Nagari Aie Dingin, Kabupaten Solok. They are  Sands, Clay, Sandstone, Limestone, and Granite. Sandstone, Limestone and Clay dominate rock structure in Jorong Koto Baru